ChemInform Abstract: 1, 5‐Benzodiazepine‐2, 4‐diones: Synthesis, Reactivity, Physico‐Chemical and Biological Properties. Issue 18 (May 2015) - Kandri Rodi, Y.; Misbahi, K.; Essassi, E. M.
Abstract Review: 65 refs.